Implantation of various energy metallic ions on aluminium substrate using a table top laser driven ion source. (26th February 2014) - Ahmad, Rabia; Rafique, M. Shahid; Tahir, M. Bilal; Malik, Huma
Abstract Particle acceleration is an important tool in material modification and several other applications. There are multiple techniques to generate and accelerate ion beams. In the current research work, ions emitted from laser induced plasma were accelerated by employing a DC high voltage extraction assembly. The Nd:YAG laser (1064 nm) with 10 mJ energy and 12 ns pulse width was irradiated on Aluminum target. Thomson parabola technique using Solid State Nuclear Track Detector (CR-39) was employed for measurement of ions energy generated from laser induced plasma. In response to a stepwise increase in acceleration potential from 0–10 kV, an evident increase in energy, in the range 627–730 keV, was observed. In order to utilize this facility as an ion source, Aluminum was exposed to these ions. The Optical and AFM micrographs revealed that the damage produced by the ions on Al surfaces, become more prominent with the increase in ion energy. TRIM simulations were performed for the analysis of the damage at the irradiated samples. Changes in the total displacements, target vacancies and replacement collisions, calculated by TRIM simulation, were analyzed for ion irradiations with increasing ion energies.